Analyzing The Role of The Audit Committee in Good Corporate Governance: Influence on Transparency and Accountability of Financial Reports - Imelda, Imelda; Mukhtaruddin, Mukhtaruddin; Kartasari, Shelly Febriana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
This article aims to improve the effectiveness of the audit committee's supervisory and monitoring tasks, to encourage transparency and accountability of a company's financial statements in order to create good corporate governance. This study was conducted by collecting data through qualitative methods based on literature reviews from various sources including research articles, online news, and relevant journals. The study uses international-based articles such as sciendirect, scopus, emerald and sinta with publication years 2020-2025. This study finally used 30 relevant journals. The role of audit committee characteristics in corporate governance, such as board size, board independence, and board expertise have a significant influence on creating good corporate governance. Although some studies still provide inconsistent results regarding the application of characteristics and are considered to be an opportunity for manipulation of a company's financial reporting. A good corporate governance system is needed to resolve agency conflicts, such as monitoring, supervising business operations, and making the right decisions to reduce errors or fraud that may occur in a company. This study contributes to the basis for further research on the problems that occur regarding the characteristics of the audit committee.